2011
DOI: 10.1371/journal.pone.0028481
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Canine Plasminogen with Streptococcus pyogenes Enolase: They Bind to One Another but What Is the Nature of the Structures Involved?

Abstract: For years it has been clear that plasminogen from different sources and enolase from different sources interact strongly. What is less clear is the nature of the structures required for them to interact. This work examines the interaction between canine plasminogen (dPgn) and Streptococcus pyogenes enolase (Str enolase) using analytical ultracentrifugation (AUC), surface plasmon resonance (SPR), fluorescence polarization, dynamic light scattering (DLS), isothermal titration calorimetry (ITC), and simple pull-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 60 publications
1
32
0
Order By: Relevance
“…In our previous work we showed that anything that leads to a non-native Str enolase or Pgn would promote binding of the two [2]. Accordingly, procedures that involve Western blotting or covalent binding of Str enolase or washing with acids/bases induce non-native conformations of the two proteins and promote binding.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work we showed that anything that leads to a non-native Str enolase or Pgn would promote binding of the two [2]. Accordingly, procedures that involve Western blotting or covalent binding of Str enolase or washing with acids/bases induce non-native conformations of the two proteins and promote binding.…”
Section: Discussionmentioning
confidence: 99%
“…Very recent investigations of enolase from S. pyogenes observed that the conformation and surface association of the enzyme are critical factors in its level of interaction with plasminogen [20,21]. Particularly of interest is that experiments intended to replicate common binding assay conditions did not observe interaction between S. pyogenes enolase and dog plasminogen until the enolase had been exposed to denaturing conditions strong enough to influence conformation and catalytic activity [21].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the 1W6T structure points out that the lysines of the third catalytic loop's plasminogen binding motif would be exposed regardless of the loop's open or closed conformation [19]. Recent studies have had mixed results regarding the importance of the plasminogen binding motif or its lysines [14,15,21]. Particularly in light of the studies that demonstrated a relationship between plasminogen affinity and structural changes induced by denaturation [21], we suspect that these varied results may be due to the flexibility and conformational variance of the third catalytic loop, and the consequential changes in solvent accessibility and structural factors yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In either case, our data suggest that once secreted by a yet-unknown mechanism, enolase probably localizes on the bacterial surface by reassociation. Although the nature of secreted enolase binding to the L. interrogans surface and the identity of the cellular receptor remain interesting subjects of future investigation, a recent study involving Streptococcus pyogenes raises an intriguing possibility that cell surfaces play a role in enolase-Pg interaction [54]. The interaction of enolase with the cell surface is thought to produce a conformation of enolase capable of binding to host plasminogen.…”
Section: Discussionmentioning
confidence: 99%